Analisis Kemampuan Pemahaman Konsep Matematis Siswa pada Materi Teorema Pythagoras Spesifik Kebudayaan Adat Melayu Kepulauan Riau - Simanjuntak, Friska Yanti; Asmaul Husna; Nailul Himmi Hasibuan (AB-JME: Al-Bahjah Journal of Mathematics Education, 2025)
This research aims to determine and analyze the mathematical concept comprehension abilities of eighth-grade junior high school students on the topic of the Pythagorean Theorem, as well as to foster a sense of nationalism among students towards the Malay cultural heritage of the Riau Archipelago. The method applied in this research is descriptive qualitative. The subjects of this study are 30 eighth-grade students from SMP Negeri 3 Batam in the 2024/2025 academic year. The test instrument used in this research consists of 3 essay questions on the Pythagorean Theorem material specific to the Malay cultural customs of the Riau Archipelago. The keywords in this article are "mathematical concept understanding ability and the Pythagorean theorem." The research results show that the mathematical concept comprehension ability of eighth-grade students at SMP N 3 Batam regarding the Pythagorean Theorem material, specifically within the context of the Malay culture of the Riau Archipelago, is still categorized as low with a percentage of 39, 45%. The results of this research are expected to assist other researchers and educators in providing everyday problem examples related to the Pythagorean Theorem material.